2021
DOI: 10.1051/e3sconf/202125501048
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of investment processes in renewable energy sector

Abstract: The purpose of the article is to assess the pace of capital contribution and investment in solar energy in order to increase the energy security of national economies. The study analyzes the development of the global solar industry for years 2009-2019 in the context of investment support. The main stages of development of world solar energy are marked and the priority of countries and regions is determined. Factors of attractiveness of solar energy for private investment are noted, namely the investment climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, this finding is in line with that of Wang et al ( 2019 ), who found that capital intensity stimulates modern energy transition in the long run but not in the short run for China from 1978 to 2015. Moreover, Savina et al ( 2021 ) argue that capital intensity influences the solar energy market.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this finding is in line with that of Wang et al ( 2019 ), who found that capital intensity stimulates modern energy transition in the long run but not in the short run for China from 1978 to 2015. Moreover, Savina et al ( 2021 ) argue that capital intensity influences the solar energy market.…”
Section: Resultsmentioning
confidence: 99%